Using a mobile application (“PrimaKu”) to promote childhood immunization in Indonesia: A cross-sectional study - Nurhaeni, Nani; Chodidjah, Siti; Adawiyah, Robiyatul; Astuti, Astuti (Belitung Nursing Journal, 2021)
Background: Universal immunization coverage among children in Indonesia is low compared to the global target. Many children in Indonesia are not fully immunized as recommended by the government, which results in a high mortality rate. The government has developed a mobile application (PrimaKu) to provide information on vaccinations and reminder features. However, the successful use of the immunization features of the app has not been widely studied. Objective: This study aimed to evaluate the use of PrimaKu on maternal attitudes toward immunization and complete basic immunizations status among Indonesian children aged 12 to 24 months. Methods: A cross-sectional research was conducted at a public health center in West Java Province, Indonesia, from August to December 2020. Convenience sampling was used to select the respondents. Data were collected using validated questionnaires and analyzed using binomial logistic regression. Results: A total of 119 mothers were included. About 44.5% of children had a complete basic immunization status. Mothers who had a supportive attitude toward immunization were 3.58 times (95% CI 1.49-8.57, p 0.003) more likely to complete the basic immunization, and those who used the mobile app were 3.23 times (95% CI 1.18-8.87, p 0.034) more likely to complete the immunization.  Conclusion: Using the PrimaKu mobile application could increase maternal attitudes toward immunization and complete basic immunization status. Therefore, public health nurses should provide comprehensive education and improve mothers’ literacy to use the application.